BRIDGING THE MORPHOLOGICAL GAP: COGNITIVE PROCESSING, READING EFFICIENCY, AND COMPREHENSION STRATEGIES IN HIGHLY AGGLUTINATIVE LANGUAGES: https://doi.org/10.5281/zenodo.20823439 - Jo‘rayev , Muhammadrahimxon (Scientific practical conference, 2026)
One of the main factors for non-native speakers having problems in understanding texts written in agglutinative languages is the lack of knowledge of the morphological rules that are used in these languages. The syntactic structures of non-agglutinative languages, which mainly rely on the word order to express the meaning, are often very rigid and do not present any problem for non-native speakers. However, agglutinative languages present a lot of syntactic variation that is mainly solved by the morphology. The use of affixes (prefixes, root vowel changes, infixes and suffixes) to form new words that express a wide range of grammatical meanings, often within a single word, makes the words of agglutinative languages very complex and very long. Thus, the main problem that non-native speakers have when understanding texts written in agglutinative languages is the decoding of the words that are used in these texts. The number of words that a non-native speaker has to learn in order to be able to read and write a text is, therefore, very high, and this number can be even higher if the non-native speakers do not have enough practice in using the morphological patterns of the target language that are needed to form words that are used in the texts that they read.